International antitrust litigation : conflict of laws and coordination - Basedow, Jürgen, 1949-2023; Francq, Stéphanie; Idot, Laurence (Studies in private international law, 2012)
The decentralisation of competition law enforcement and the stimulation of private damages actions in the European Union go hand in hand with the increasingly international character of antitrust proceedings. As a consequence, there is an ever-growing need for clear and workable rules to co-ordinate cross-border actions, whether they are of a judicial or administrative nature: rules on jurisdiction, applicable law and recognition as well as rules on sharing of evidence, the protection of business secrets and the interplay between administrative and judicial procedures. This book offers an in-d.